Fritillaria shahuensis (Liliaceae), a new species from western Iran - Advay, Mahfouz; Rix, Martyn (Phytotaxa, 2024)
A new species, Fritillaria shahuensis, from western Iran is described. It is similar in general facies to F. atrolineata and F. chlorantha in the F. caucasica-group but differs mainly in colour and size of lowest leaves and shape and colour of perigone segments. Fritillaria shahuensis is also similar in general facies to F. assyriaca and F. kordestanica but differs mainly by colour of perigone segments. Detailed taxonomic descriptions, diagnostic characters, original photographs, geographical distributions, habitat, phenology and ecology, etymology and conservation status of the new and related species are presented.